53. IGRT Cone Beam CT: Patient specific organ dose evaluation. (December 2018) - Gallio, E.; Giglioli, F.R.; Rossetti, V.; Fiandra, C.; Ropolo, R.; Rampado, O.
Abstract : Purpose: Daily images from CBCT could deliver significant dose to the patient, which should be considered and evaluated. It is essential to associate the absorbed dose delivered by the imaging procedures to the treatment of each patient. Aim of this work is to calculate organ doses for patients undergoing Cone Beam CT (CBCT) when treated with radiotherapy. Methods: The system in use was an Elekta CBCT (XVI) and the protocols analysed were four: head, pelvis, chest and chest 4D with different parameters. The formula for organ dose calculation was obtained from Rampado et al.[1] where dose to organs were evaluated by means of Monte Carlo simulation in phantom; the effect of patient size were also accounted for. Dose to organs involved in CBCT scans is: D T = D W, 1 Ph · ( D T / D W, 1 Ph ) tab · a · e - bx where D W, 1 Ph is the measured dose in a phantom for the specific protocol, x is the effective diameter of the patient, ( D T / D W, 1 Ph ) tab, a and b are tabulated data from the article cited above. Patients were analyzed from March to June 2017. For each case were registered: the effective diameter from simulation CT, CBCT protocol, number of CBCT scans. Results: Two hundred patients were considered. For head protocol, the mean CBCT doses were about 20 ± 10 mGy for all organs. Instead, doses of about 400 ± 150 mGy were evaluated for pelvis protocol. CBCT Doses for Chest 4D protocol were lower than other chest ones (about 50 ± 25 mGy vs 400 ± 150 mGy). This difference was due to number of CBCT scans/treatment fractions. Conclusions: Doses from CBCT procedures should be accounted for; based on organ doses calculation, a program of dose optimization could be performed.